SPE Rocky Mountain Regional Meeting 1988
DOI: 10.2118/17542-ms
|View full text |Cite
|
Sign up to set email alerts
|

Permeability Damage to Natural Fractures Caused by Fracturing Fluid Polymers

Abstract: Formation damage studies using artificially fractured, low-permeability sandstone cores indicate that viscosified fracturing fluids can severely restrict gas flow through these types of narrow fractures. These studies were performed in support of the Department of Energy's Multiwell Experiment (MWX). The MWX program was a coordinated research effort to study methods to evaluate and enhance gas production from low-permeability lenticular reservoirs of the Western United States. Extensive geolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Studies [257] on formation damage using artificially fractured, low permeability sandstone cores indicated that viscosified fracturing fluids can severely restrict the gas flow through narrow fractures. Poly(saccharide) polymers such as hydroxypropyl guar, HEC, and xanthan gum caused a significant reduction of the gas flow through the cracked cores, up to 95%.…”
Section: Formation Damage In Gas Wellsmentioning
confidence: 99%
“…Studies [257] on formation damage using artificially fractured, low permeability sandstone cores indicated that viscosified fracturing fluids can severely restrict the gas flow through narrow fractures. Poly(saccharide) polymers such as hydroxypropyl guar, HEC, and xanthan gum caused a significant reduction of the gas flow through the cracked cores, up to 95%.…”
Section: Formation Damage In Gas Wellsmentioning
confidence: 99%
“…Studies (Gall et al, 1988) on formation damage using artificially fractured, low permeability sandstone cores indicated that viscosified fracturing fluids can severely restrict the gas flow through narrow fractures. Polysaccharide polymers, such as hydroxypropyl guar, HEC, and xanthan gum caused a significant reduction in gas flow through the cracked cores, by up to 95%.…”
Section: Formation Damage In Gas Wellsmentioning
confidence: 99%
“…In some cases, increased viscosity, fluid volumes, or inadequately size fluid loss material can reduce productivity by damaging the fracture systems or failing to effectively counteract PDL. [22][23][24][25][26] In laboratory tests designed to model PDL behavior, it has been found that proper sizing and concentration of fluid loss material is essential for PDL control. 26 Further, increasing the fluid viscosity or gelling agent can sometimes dilate fissures or enhance the PDL effects, which can be potentially damaging.…”
Section: Perforatingmentioning
confidence: 99%